Utilization of Mosques as Learning Means for Islamic Education During the Abbasid Dynasty - Lubis, Mayang Sari; Siregar, Asrul; Wahyuni, Sri; Yamin, Muhammad; Irham, Muhammad (Jurnal Riset Ilmu Pendidikan, 2025)
The Abbasid Dynasty has produced many important figures who made great contributions to the development of Islamic civilization. Caliphs such as Abu al-Abbas alSaffah, Abu Ja'far al-Manshur, Harun ar-Rasyid, and Al-Ma'mun played a very good role in advancing the Abbasid Caliphate, both in terms of politics, economy, and science. It should be noted that the Abbasid Dynasty was an Islamic government that implemented a more open and tolerant policy towards non-Muslims, such as Christians, Jews, and Zoroastrians. Thus, giving birth to pluralism, thus encouraging the development of more diverse science and culture. The purpose of this study is to determine the learning methods used in mosques during the Abbasid Dynasty and to analyze the influence of mosques on the development of Islamic science and education during the Abbasid Dynasty. This research was conducted using a literature review system approach. This approach views existing literature as part of an interrelated system, where each element (theory, concept, research findings) influences and interacts with each other to form a more comprehensive understanding. The results of this study indicate that the characteristic of the peak of the glory of the Abbasid Dynasty was significant progress in the field of science, marked by the large number of Muslim scientists in the Abbasid era and the main factor in the glory of the Abbasid Dynasty was the establishment of Bait al-Hikmah, kuttab, and mosques as centers of learning at that time.